2018
DOI: 10.1016/j.disc.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

A sufficient condition for DP-4-colorability

Abstract: DP-coloring of a simple graph is a generalization of list coloring, and also a generalization of signed coloring of signed graphs. It is known that for each k ∈ {3, 4, 5, 6}, every planar graph without C k is 4-choosable. Furthermore, Jin, Kang, and Steffen [9] showed that for each k ∈ {3, 4, 5, 6}, every signed planar graph without C k is signed 4-choosable. In this paper, we show that for each k ∈ {3, 4, 5, 6}, every planar graph without C k is 4-DP-colorable, which is an extension of the above results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…More specifically, we are interested in finding sufficient conditions for a planar graph to be DP -4-colorable. The next result of Kim and Ozeki [5] provides an important motivation for our research. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 92%
“…More specifically, we are interested in finding sufficient conditions for a planar graph to be DP -4-colorable. The next result of Kim and Ozeki [5] provides an important motivation for our research. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 92%
“…Kim and Ozeki [6] showed that planar graphs without 4-cycles are DP-4-colorable. Some more sufficient conditions for a planar graph to be DP -4-colorable have been found in [2,6,7,9,10], and we summarize them below. 6,7,9,10]) The following planar graphs are DP-4-colorable (3,5), (3,6), (4,5), (4, 6)}.…”
Section: Introductionmentioning
confidence: 99%
“…Case 4.1. H 4 is isomorphic to one of Figure 1 (4)- (6). By (R1), H 4 gets 1 2 · 4, 1 2 · 6, 1 2 · 6 from adjacent 8 + -faces in (4), (5), (6), respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations